Math Problem Statement
simplify (𝒑 ∧ (𝒑 → 𝒓 ∨ 𝒒)) ∧ (𝒓 → 𝒒)
Solution
We can simplify the expression using the basic rules of propositional logic.
Step-by-step simplification:
-
Implication rule: Recall that is logically equivalent to .
So, we rewrite:
-
Implication rule: Similarly, is equivalent to .
So now, the expression becomes:
-
Distributive property: Distribute across :
-
Tautology elimination: The term is a contradiction, so it simplifies to false ().
Now, the expression is:
Which simplifies to:
-
Distributive property: Expand :
We can distribute the terms:
-
Further simplification:
- Consider the inner terms . By distributive property:
- Simplifying this: This simplifies to: Which further simplifies to:
Now, we substitute this back:
Final simplified expression:
Would you like more details on any of these steps or have any other questions?
Here are 5 related questions:
- How does the implication rule work in logic?
- What is the distributive property in logic?
- Why does simplify to false?
- Can tautologies simplify more complex logical expressions?
- How would adding another condition to the expression affect the simplification?
Tip: Remember that conjunctions with contradictions () or tautologies simplify very easily, helping reduce complex expressions quickly.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Propositional Logic
Logical Equivalences
Implication Rule
Distributive Property
Formulas
Implication: p → q is equivalent to ¬p ∨ q
Distributive Property: a ∧ (b ∨ c) is equivalent to (a ∧ b) ∨ (a ∧ c)
Theorems
Tautology and Contradiction Elimination
De Morgan's Laws
Suitable Grade Level
Undergraduate Level - Introduction to Logic
Related Recommendation
Simplify (p ∧ q) ⟹ r Using Logical Equivalences - Step-by-Step Guide
Simplify Logical Expression Using Boolean Laws: Step-by-Step Solution
Simplify Logical Expression ¬(¬p ∨ r) → (q → p), q → (p ∨ r)
Logical Equivalence of p ∧ (q ∨ r): Analysis and Equivalent Expressions
Simplifying the Propositional Logic Statement P → (Q → P ∧ Q)